2021
DOI: 10.3389/fonc.2021.736640
|View full text |Cite
|
Sign up to set email alerts
|

High Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio Are Associated With Sarcopenia Risk in Hospitalized Renal Cell Carcinoma Patients

Abstract: PurposeThis study aimed i) to identify the best cutoff points of neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) that predict sarcopenia and ii) to illustrate the association between sarcopenia risk and NLR or PLR in renal cell carcinoma (RCC) patients undergoing laparoscopic partial or radical nephrectomy.MethodsA total of 343 RCC patients who underwent laparoscopic partial or radical nephrectomy between 2014 and 2019 were enrolled in our study. Sarcopenia was assessed by lumbar skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
5
9
0
Order By: Relevance
“…Taking a wide range of inflammatory variables previously reported that could be linked to RCC prognosis into consideration was one of the strengths of this study. The diagnostic criteria and prevalence of sarcopenia (34.8% of total 276 patients) were similar to the reported studies in RCC (4,16). What we found between sarcopenia and greater OR; odd ratio, CI; confidence interval, NLR; neutrophil-to-lymphocyte ratio, LMR; lymphocyte-to-monocyte ratio, PLR; platelet-to-lymphocyte ratio, SII; systemic immune-inflammation index, PNI; prognostic nutritional index, mGPS; modified Glasgow Prognostic Score.…”
Section: Discussionsupporting
confidence: 85%
“…Taking a wide range of inflammatory variables previously reported that could be linked to RCC prognosis into consideration was one of the strengths of this study. The diagnostic criteria and prevalence of sarcopenia (34.8% of total 276 patients) were similar to the reported studies in RCC (4,16). What we found between sarcopenia and greater OR; odd ratio, CI; confidence interval, NLR; neutrophil-to-lymphocyte ratio, LMR; lymphocyte-to-monocyte ratio, PLR; platelet-to-lymphocyte ratio, SII; systemic immune-inflammation index, PNI; prognostic nutritional index, mGPS; modified Glasgow Prognostic Score.…”
Section: Discussionsupporting
confidence: 85%
“…A meta-analysis showed that patients with sarcopenia had worse OS (HR = 1.76; 95% CI, 1.35–2.31; P < 0.001). In addition, our previous studies confirmed that sarcopenia was an independent prognostic risk factor for patients with RCC ( 16 , 17 , 28 ).…”
Section: Discussionsupporting
confidence: 65%
“…Hu et al also noted that NLR was an independent predictor for sarcopenia risk. 44 Our results showed that higher NLR values increased the likelihood of sarcopenia in males by 62%, but not in females. However, not all studies support the findings observed in the studies mentioned above.…”
Section: Discussionmentioning
confidence: 47%